Análise comparativa de tecnologias para avaliação de composição corporal em comparação com a absorciometria de raios-X de dupla energia em indivíduos saudáveis - Queiroz, Larissa Luna (2022)
There is a diversity of equipment for the prediction of body composition in our country. For professionals working with this type of evaluation or for researchers, it is increasingly difficult to know which device to trust. Therefore, it is necessary to look for evidence of which equipment provides reliable results. However, few studies have compared the indirect forms of assessment with the gold standard, double-absorption X-ray disintometry. Therefore, this study aims to compare different methods of assessing body composition used in clinical practice – DEXA, bioimpedance and adipometer. This cross-sectional, quantitative research was carried out at the Clinical Research Unit of the University Hospital Walter Cantídio/UFC. The sample consisted of 382 adult men and women. The percentage of fat was significantly (p<0.001) different between genders. All devices were reliable in men and women, as indicated by high intraclass correlation coefficients for fat percentage: adipometer (0.947); Renpho® BIAs (0.831); Omron® HBF-306c (0.927); Omron® HBF-514c (0.928); Inbody® H20N (0.948); Inbody® 770 (0.964). After adjusting for sex and body mass index (BMI), both the strength of correlation and agreement changed. Body composition analyzers suffer changes in the correlation according to sex and BMI, which suggests that the method to be used in the assessment of patients takes these factors into account, and it is not necessary to seek complex technologies for the analysis of body composition in adults healthy.